From juniors to seniors: changes in training characteristics and aerobic power in 17 world-class cross-country skiers - Walther, J.; Haugen, T.; Solli, G. S.; Tonnessen, E.; Sandbakk, Ø. (Frontiers in Physiology, 2023)
Purpose: To compare training characteristics and aerobic power (VO2max) between the most successful junior and senior seasons of world-class cross-country (XC) skiers and to identify differences between sexes and among sprint and distance skiers.